QUANTIFYING PROLINE AND TOTAL PHENOLIC CONTENT AS BIOMARKERS FOR DROUGHT RESILIENCE IN MUNGBEAN (VIGNA RADIATA L.) CULTIVARS - SHAHEEN, A; FARIDI, R; KHAN, SA; MALIK, S; PARVEEN, A; SALEEM, F; FARZAND, M; RAZA, A; BIBI, A; WALYAT, S; SHABBIR, F (Biological and Clinical Sciences Research Journal, 2024)
Mungbean (Vigna et al.) belongs to the Fabaceae family. It has two planting seasons (spring and summer). Mungbean is a crop in arid and barren areas. These areas are more prone to water stress. The present study evaluated water stress’s effect on green gram to find its resistance to drought stress. A controlled experiment was conducted under factorial CRD with three replications and two factors varieties and water levels (A set of 15 genotypes was obtained from the NIAB research institute, Faisalabad. Firstly, the total phenolic content (TPC) test analyzed these genotypes. The five varieties that showed high TPC were used for experiments such as NM-98, Abbas Mung, NM-121-25, NM-2016, and NM-92) at the experimental area of Plant Breeding and Genetics, University of Agriculture, Faisalabad, during the spring season of 2023. Three levels of water stress were applied. Data were recorded for different traits under water stress at different growth stages of mungbean. Analysis of variance was performed to see the significant difference among treatments, Tukey’s HSD test was applied for the mean comparison test using Statistix 8.1 statistical software, and correlation analysis was performed to check the relationship between different traits. An increase in root length, proline content, and total phenolic content positively affected drought tolerance. The performance of NM-121-25 was better than that of others, and the interactive values of NM-2016 were better than those of others at different drought levels. Pod length, leaf number per plant, relative water content, membrane stability index, leaf area, and proline content showed significant positive results with plant yield.